∛(30x + 36) - ∛(30x-55) = 1;
## ∛(30x + 36) = 1 +∛(30x-55); elevo al cubo ambos lados:
30x+36 = 1+3∛(30x-55)+3[∛(30x-55)]^2 + 30x-55;
36 = 1+3∛(30x-55)+3[∛(30x-55)]^2 -55;
90 = 3∛(30x-55)+3[∛(30x-55)]^2;
90 =3 ∛(30x-55) * { 1 + [∛(30x-55)]);
30 = ∛(30x-55) * { 1 + [∛(30x-55)]); reemplazo con la igualdad ##
30 = ∛(30x-55) *∛(30x + 36); elevo al cubo:
27000 = (30x-55)(30x+36);
27000 = 900x^2 - 1650x + 1080x - 1980;
0 = 900x^2 - 570x - 28980;
0 = 90x^2 - 57x - 2898;
0 = 30x^2 - 19x - 966; Baskara:
[19+-√(361 +115920)] / 60;
(19 +- 341) / 60;
x = (-161/30); o: x= 6;